Aqueous ball milling of nacre constituents facilitates directional self-assembly of aragonite nanoparticles of the gastropod Haliotis glabra - Lemloh, Marie-Louise (J R Soc Interface, 2017)
A ball-milling approach was developed to investigate the constituents of isolated nacre tablets of the gastropod Haliotis glabra in aqueous suspension without additional chemical additives. The obtained particle mixtures were characterized using X-ray crystallography as well as scanning and transmission electron microscopy. Aragonite nanoparticles retained their crystal structure even after 14 h of ball milling. The long-term stability of the particle mixtures varied as a function of the ball-milling duration. An increased milling time led to rod-like stable assemblies of aragonite nanoparticles. Selected area electron diffraction investigations revealed that the longitudinal axes in about one-third of these nanoparticle rods were oriented along the crystallographic c-axis of aragonite, indicating oriented attachment of the aragonite nanoparticles. These in vitro observations support the idea that a two-stage process, separated into crystallization of nanoparticles and oriented assembly of nanocrystals, could also occur in vivo.